«Equilibrando las cuentas» - Ashencaen Crabtree, Sara (2023)
Strongly emerging Indigenous methodologies have attracted researchers to employ diverse research paradigms within a moral commitment to conducting research based on ethical sensitivities and appropriate research protocols, as informed by research work with marginalized and unfamiliar groups including Indigenous Communities. However, adopting Indigenous methodological approaches may raise additional ethical considerations requiring a nuanced examination of what these may entail and competing ethical claims regarding research funding, research processes, outcomes and output. In this article, we draw sociological insights from Bourdieusian theory, as well as feminist epistemology, to explore the ethical implications arising from qualitative research the authors recently completed with Indigenous communities in equatorial Malaysia and Costa Rica, where Indigenous land rights and access issues form the contextualizing and comparative backdrop to the study, with reference to relevant international UN policies such as the Sustainable Development Goals.